Bioassays advanced methods and applications - Häder, Donat-Peter; Erzinger, Gilmar S. (Elsevier, 2018)
Bioassays: Advanced Methods and Applications provides a thorough understanding of the applications of bioassays in monitoring toxicity in aquatic ecosystems. It reviews the newest tests and applications in discovering compounds and toxins in the environment, covering all suitable organisms, from bacteria, to microorganisms, to higher plants, including invertebrates and vertebrates. By learning about newer tests, water pollution control testing can be less time and labor consuming, and less expensive. This book will be helpful for anyone working in aquatic environments or those who need an introduction to ecotoxicology or bioassays, from investigators, to technicians and students.--Provided by publisher.